Effective strategies for EFL teachers of visually impaired learners: a research synthesis - Rodríguez Salinas, Evelyn Vanessa (2023)
Visual impairments have been a social problem worldwide and very few countries invest in resources to train EFL teachers and thus educate students with these impairments. In addition, there is a limited amount of research that proposes teaching strategies and methodologies for this student group. In other words, studies focused on people with visual impairments are scarce in general. Promoting inclusive education is everyone's responsibility to ensure the development of students with disabilities. Instructors must provide learners an inclusive teaching- learning environment that supports successful English language teaching. The present research aims to identify effective strategies for teachers of English as a foreign language (EFL) in the teaching process for learners with visual impairments. A retrospective, observational, and analytical study was carried out, prioritizing the collection of data from high-impact scientific articles, meta-analysis, and surveys with teachers that have experience with visually impaired learners, with a qualitative and quantitative approach. The data collected was obtained through surveys with 55 expert teachers in the subject that have had effective teaching results. Teachers mentioned that some of the most effective strategies included auditory tools, sensory instruments, and reading systems technology. At the conclusion of this study, it was identified the ineffective strategies and obsolete models, as well as new approaches and activities to support the continuous improvement in the four language skills. Once the study was carried out, a guide of teaching strategies was developed to support EFL teachers of students with visual impairments.